Design of Linear Model for Water Hardness Removal by Activated Coconut Shell Carbon using Design of Experiment Method - Sundera Raj, Diviyan Raj (Universiti Teknologi PETRONAS, 2017)
The present study reports the water softening by adsorption of hardness ions onto Activated Coconut Shell Carbons. In the previous study, it was found that 500°C Activated Coconut Shell Carbon removed more hardness ions compared to coconut shell carbons (400, 500°C) and the other activated carbon (400°C). Therefore, 500°C ACSC was selected and used as the adsorbent for batch experiments. Characterization of Activated Coconut Shell Carbon was identified by Fourier Transform Infrared Spectroscopy and Scanning Electron Microscopy techniques. Batch experiments were carried out to determine the effect of various adsorbent factors such as adsorbent dose, pH, and contact time, on the adsorption process using synthetic water samples. Full Factorial Design with centerpoints (0,0) was used to determine the optimal values of parameters that provide the highest removal efficiency. The number of experiments carried out were based on the levels of each parameter, number of replicates and number of centerpoints. The total number of experiments was 28.